Effect of physical activity in treatment of paediatric obesity - Pastucha, Dalibor; Malinčíková, Jana; Horák, Svatopluk; Povová, Jana; Konečný, Petr (Central European Journal of Public Health, 2015)
The aim of the study was to compare the differences in anthropometric parameters, maximal oxygen uptake (VO₂max) and physical activity (PA) between groups of 146 obese boys and 128 obese girls. We tried to describe the relationships between changes in PA and changes in VO₂max, body fat, weight, waist circumference and hip circumference. We found statistically significant changes in VO₂max and waist circumference only in the group of boys and significant changes in VO₂max in the group of girls.
Keywords: pohybová aktivita; Czech Republic; obvod pasu; lidé; ženské pohlaví; mladiství; antropometrie; Waist Circumference; Adolescent; Pediatric Obesity; Female; mužské pohlaví; tělesná výkonnost; spotřeba kyslíku; Anthropometry; Motor Activity; Child; obezita dětí a dospívajících; Physical Fitness; Humans; Male; Oxygen Consumption; Česká republika; dítě